The Correlation between Preoperative Average Heart Rate and Postoperative Recurrence in Patients with Paroxysmal Atrial Fibrillation Undergoing Transcatheter Radiofrequency Ablation - Xiu Feng; Ling Yang; Zhenni Yang; Yuxia Miao; Mingxia Gong; Jun Meng; Min Xu (Reviews in Cardiovascular Medicine)
Background: Atrial fibrillation (AF) is the most common persistent arrhythmia, with increasing incidence worldwide. Transcatheter radiofrequency ablation (RFA) represents a first-line therapy for paroxysmal atrial fibrillation (PAF), although the long-term recurrence rate of AF remains relatively high. This study aimed to investigate the relationship between the average heart rate (AHR) on a dynamic electrocardiogram before transcatheter RFA and the postoperative recurrence of AF in patients with PAF. Methods: A retrospective analysis was conducted on patients with PAF who experienced primary transcatheter RFA. Relevant clinical indicators, dynamic electrocardiograms, and echocardiography were collected from the enrolled patients before ablation. Multivariate logistic regression analysis examined the relationship between the preoperative AHR and postoperative recurrence of AF in patients with PAF. Results: This study included 224 patients with PAF who were scheduled for transcatheter RFA. Based on the AHR in sinus rhythm state on the dynamic electrocardiogram before ablation, the patients were divided into three groups: low, medium, and high heart rate. The recurrence rates of AF after ablation for the three groups were 14.667%, 8.108%, and 4.000%, respectively. After adjusting for confounding factors, postoperative AF recurrence risk gradually decreased with an increase in preoperative AHR (odds ratio: 0.849, 95% confidence interval: 0.729–0.988, p = 0.035). This trend remained statistically significant even after adjusting for the three categorical variables of AHR (odds ratio = 0.025, 95% confidence interval: 0.001–0.742, p = 0.033). The curve fitting analysis indicated a linear and negative correlation between the preoperative AHR and postoperative AF recurrence risk in patients with PAF. Conclusions: In patients with PAF who experienced their primary transcatheter RFA, there was a linear and negative correlation between the AHR in sinus rhythm state on the preoperative dynamic electrocardiogram and the risk of postoperative AF recurrence.